AN INVESTIGATION OF SCHOOL-BASED CHALLENGES FACING THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN THE PRIMARY SCHOOLS IN MALAWI: A CASE STUDY OF FOUR PRIMARY SCHOOLS IN ZOMBA DISTRICT - Chirwa , Grames; Lingolwe, Francis; Naidoo, Devika (International Journal of Online and Distance Learning, 2021)
Purpose: This study sought to investigate the challenges which schools are facing in implementing inclusive education in mainstream primary schools in Zomba district. Methodology: Qualitative research method which employed a case study design was used. Thirty-four participants were involved in this study. These were purposely sampled. Data was collected through interviews, documents review and classroom lesson observations to provide methodological triangulation. Data was analyzed using thematic content analysis method inductively. Results: The results of the study indicated that the implementation of inclusive education is facing a number of challenges such as ineffective orientation of head teachers and teachers to inclusive education, unavailability of teaching and learning materials for special needs learners in the mainstream schools, lack of special needs specialist teachers and lack of infrastructure suitable for the diverse special education needs learners. Unique contribution to theory and practice: The study recommended, that the Ministry of Education, Science and Technology officers, that is the District Education Managers and the Primary Education Advisors involved in the implementation of inclusive education need to ensure that there is effective orientation training of the head-teachers teachers and teachers on inclusive education. The Ministry of education, Science and Technology should provide teaching and learning materials for the special education needs learners in the mainstream schools.